Performance-Based Placement Design of Tuned Electromagnetic Inertial Mass Dampers - Nakamura, Yutaka; Hanzawa, Tetsuya (Frontiers in Built Environment, 2017)
This paper presents a performance-based placement design method for the control of the earthquake responses of a multi-story building using tuned electromagnetic inertial mass dampers (T-EIMD). The T-EIMD consists of a ball screw mechanism, a gear, a flywheel, and an electric generator installed in a cylinder, and a spring element connected in series. The ball screw mechanism converts the axial oscillation of the rod end into the rotational motion of the internal flywheel, and generates a large inertial force. The electric generator is turned by the rotation of the inner rod and generates a variable damping force that is controlled by the terminal resistance. The T-EIMDs are installed between adjacent floors of a building with steel chevron braces, and function as large tuned mass dampers within the stories. The spring element has the function of tuning the natural period of the T-EIMD to the fundamental natural period of the building. In the present work, a design procedure for the story-wise placement of T-EIMDs is proposed to limit the peak story drift angles to a specified target value. The proposed procedure utilizes the expanded complete quadratic combination (CQC) method that involves modal analysis with complex eigenvalue analysis, and is able to determine the necessary story-wise distribution of inertial masses of the T-EIMDs in a building. Time history earthquake response analyses are carried out for multi-story building models set up with the necessary number of T-EIMD units, and the results establish the effectiveness and the adequacy of the proposed performance-based placement design procedure.